2022
DOI: 10.1029/2022jb023948
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxygen Fugacity on Hydroxyl Incorporation in Garnet at 1–3 GPa and 800–1000°C and Implications for Water Storage in the Mantle

Abstract: Garnet is an important mineral constituent of the deep continental crust, subducted oceanic crust, and upper mantle where garnet-bearing granulites, eclogites, peridotites, and pyroxenites are present. Studies on natural samples have shown that garnet often contains some structural OH groups ranging from several tens to thousands of ppm H 2 O (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 71 publications
0
17
1
Order By: Relevance
“…2022, Zhang et al . 2022). Previous studies have suggested that this band may be attributed to tiny inclusions of hydrous minerals (Geiger and Rossman 2020a, b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2022, Zhang et al . 2022). Previous studies have suggested that this band may be attributed to tiny inclusions of hydrous minerals (Geiger and Rossman 2020a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Based on geological and spectroscopic reasons, it was recently interpreted as OH-F substitutions by Mosenfelder et al (2022). However, this band was not present in all F-rich garnets and thus was linked to the extremely enriched Ca in grossular by Zhang et al (2022). This can explain the absence of the band in low-Ca mantle garnets.…”
Section: Assignment Of the Ir Bandmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, the incorporation of water in garnet was often assumed to be related to hydrogarnet defects, for example, by four protons replacing a Si 4+ (Ackermann et al, 1983). However, recent studies show more complexity in the assignments of water in garnet, and not only Si but also Fe, Mg, and F affect water incorporation (Mosenfelder et al, 2022;Zhang et al, 2022). The difficulty in assigning the water bands makes it difficult to place further constraints on the microscale mechanism of proton conditions in garnet.…”
Section: Conduction Mechanismsmentioning
confidence: 99%
“…Garnet (gt)-garnets cover a wide range of compositions; the solubility of a particular garnet has a strong dependence on its Mg content and the oxygen fugacity (e.g., Mookherjee & Karato 2010;Zhang et al 2022). For example, the pure pyrope endmember of garnet is significantly more water-poor than its majorite or grossular endmembers.…”
Section: Water Solubility Of Upper Mantle and Transition Zone Mineralsmentioning
confidence: 99%